Radio Frequency Integrated Circuit Design for Cognitive Radio Systems - Fahim, Amr (Springer, 2015)
This book fills an information gap on cognitive radios, since the discussion focuses on the implementation issues that are unique to cognitive radios and how to solve them at both the architecture and circuit levels. This is the first book to describe in detail cognitive radio systems, as well as the circuit implementation and architectures required to implement such systems. Throughout the book, requirements and constraints imposed by cognitive radio systems are emphasized when discussing the circuit implementation details. This is a valuable reference for anybody with background in analog and radio frequency (RF) integrated circuit design, needing to learn more about integrated circuits requirements and implementation for cognitive radio systems.